Rancang Bangun Prototype Aplikasi Point of Sale (POS) Berbasis Web Sebagai Media Simulasi dan Pelatihan Kasir pada Toko Retail Elektronik Erablue - Depsi Yulinda; Farizi Ilham; Rayhan Andika Putra; Nur Abidah Rambe (OKTAL : Jurnal Ilmu Komputer dan Sains, 2026)
The development of information technology has encouraged various business sectors to utilize computerized systems to support operational activities. One sector requiring an effective information system is electronic retail stores, which experience a large number of daily sales transactions. Cashier training processes that are still conducted directly on the main system have the potential to cause transaction errors and disrupt store operations. This study aims to design and build a prototype web-based Point of Sale (POS) application as a medium for cashier simulation and training. Data collection methods were conducted through observation, interviews, and literature review. The system was developed using the Laravel framework and a MySQL database. Key features include user login, an admin dashboard, product management, cashier transaction simulation, a shopping cart, and access rights restrictions based on user roles. Test results indicate that the system can facilitate a more structured cashier training process, improve understanding of transaction flows, and reduce the risk of errors during sales transactions. Thus, the web-based POS application can be an effective learning medium for cashiers in electronic retail stores.